The Galactic spiral structure as revealed by O- and early B-type stars. Issue 1 (17th May 2019) - Chen, B-Q; Huang, Y; Hou, L-G; Tian, H; Li, G-X; Yuan, H-B; Wang, H-F; Wang, C; Tian, Z-J; Liu, X-W
ABSTRACT: We investigate the morphology and kinematics of the Galactic spiral structure based on a new sample of O- and early B-type stars. We select 6858 highly confident OB star candidates from the combined data of the VST Photometric H  α Survey Data Release 2 (VPHAS+ DR2) and the Gaia Data Release 2 (Gaia DR2). Together with the O-B2 stars from the literature, we build a sample consisting of 14 880 O- and early B-type stars, all with Gaia parallax uncertainties smaller than 20 per cent. The new sample, hitherto the largest one of O- and early B-type stars with robust distance and proper motion estimates, covers the Galactic plane of distances up to 6 kpc from the Sun. The sample allows us to examine the morphology of the Scutum, Sagittarius, Local, and Perseus Arms in great detail. The spiral structure of the Milky Way as traced by O- and early B-type stars shows flocculent patterns. Accurate structure parameters, as well as the means and dispersions of the vertical velocity distributions of the individual spiral arms are presented.